The Importance of Education Financing Management in Islamic Institution - Rita Amelia; Hamdi Abdul Karim (FiTUA: JURNAL STUDI ISLAM, 2025)
Education financing management has a very important role in ensuring the continuity and quality of education provision. Education financing includes: education budget planning, education financing, education budget implementation, education financial accounting and accountability, and education budget audit and supervision. The success of education is highly dependent on the adequacy of available funds, how to strategically manage limited funds to meet the needs of education optimally, efficiently and effectively becomes one of the main focuses in the management of educational institutions. In the context of Islamic educational institutions, optimizing resources is key to ensuring the continuity of the learning process, improving the quality of educational services, and ensuring that educational goals are achieved as expected. In order to run effectively, education financing management requires careful planning, transparency, accountability, and good coordination between stakeholders. This research uses a qualitative method, namely by describing the facts in depth and collecting data from various sources, such as articles, books and journals that discuss the importance of financing management in Islamic educational institutions. Furthermore, it analyzes and examines the ways of managing financing in Islamic educational institutions. The results of the study show that the institution's financing management focuses on effective and efficient financial management.